2020
DOI: 10.1016/j.scitotenv.2020.141413
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of personal care products selection on greywater characteristics and reuse?

Abstract: The effects of 55 personal care and household products on greywater were studied. The toxicity of the products was also tested using Microtox® and MicroResp TM .  Product selection impacts both pollution load and character of greywater. No link could be found between the products properties and branding or price. Regardless of type and selection, the toxicities of the products appeared limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…From the perspective of the impact of untreated discharges of greywater on aquatic habitats, the ecotoxicity of chemicals contained in personal care products should also be considered [ 43 ]. Ecological status based on macroinvertebrates can be evaluated by considering multiple pressures, including land use [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of the impact of untreated discharges of greywater on aquatic habitats, the ecotoxicity of chemicals contained in personal care products should also be considered [ 43 ]. Ecological status based on macroinvertebrates can be evaluated by considering multiple pressures, including land use [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the variations did not correlate with factors typically seen as affecting consumer choice such as brand, type (eco-friendly or not) or price. The authors concluded "it is not currently possible for consumers to actively manage the issue [of greywater quality] through choice" and stress that "products labelled as eco-friendly were not seen to be less polluting or indeed less toxic" (Kadewa et al, 2020).…”
Section: Personal Care Productsmentioning
confidence: 99%
“…Depletion of freshwater resources is increasing gradually, emphasizing the need to conserve freshwater by reusing or recycling treated wastewater (Delhiraja & Philip, 2020; Noutsopoulos et al., 2018). Greywater (GW) is a type of wastewater that includes laundry, bathroom, washbasin, and kitchen excluding toilet wastewater (Kadewa et al., 2020; Shaikh & Ahammed, 2020). In particular, greywater treatment and its reuse have gained increased attention in the last few decades around the world (Shaikh & Ahammed, 2020).…”
Section: Introductionmentioning
confidence: 99%